Using PBL with FILA Chart to Design Learning Activities on Fundamental Principle of Counting to Support Problem-Solving Skills - Supot Seebut, Pariyakorn Suphap and (Journal of Community Development Research (Humanities and Social Sciences); Vol 9 No 2 (2559): May-August 2016, 2016)
The key successful in mathematical problem solving is that students could employ problem-solving skills for performing in problem-solving process related to mathematical problems posed by instructors in a mathematics classroom. However, it is found that there are many students frustrated with using problem-solving skills in practice because thinking simultaneously with mathematics problems and procedures in solving them based on problem-solving skills seem to be abstract and very difficult for students. The purposes of this study are to develop learning activities using PBL with FILA chart as a scaffolding tool applied for supporting students to use problem-solving skills in performing with mathematics problems on Fundamental Principle of Counting step by step. To determine the effect of using learning activities using PBL with FILA chart on the levels of students’ problem solving skills, three subjective tests about subject matter on Fundamental Principle of Counting are administered as posttest to student. The rubric score is employed to determine the level of students’ problem solving skills through their performing in subjective tests. Data from rubric for evaluating student’ problem solving skills is analyzed using descriptive statistics to find frequency of students identifying particular student’ skill levels in problem solving for each of essential features of problem solving skills and to compute the mean skill levels in problem solving of students for each essential features. The results have verified the significant effects that learning activities using PBL with an effect FILA chart.   Keywords: FILA Chart, Problem Based Learning, Problem Solving, Problem Solving Skills, Fundamental Principle of Counting
Keywords: FILA Chart, Problem Based Learning, Problem Solving, Problem Solving Skills, Fundamental Principle of Counting